state selection of ammonia molecular beam using tapered ring focuser (Baghdad Science Journal, 2005)
I've made extensive studies on the distribution of the electric field stable heterogeneous within intensive that contain metal rings with slope diagonal positive to a site halfway to be in its maximum value, followed by decline negative and equally to the other end of the concentrated distributed by electric stable thanking sequentially and have focused empirical studies in the pastthe molecules that you focused Pantqaúha during passage